SOCIAL CAPITAL AND SUSTAINABILITY LEVEL OF MAIZE FARM IN TANJUNG LAGO SUB-DISTRICT BANYUASIN DISTRICT - Azqia Wardani; M Yazid; Yunita - Yunita (JURNAL MANAJEMEN AGRIBISNIS, 2021)
The existence of social capital has an equally important with economic capital. Social capital is an important factor for farmers to innovate and support sustainability. Sustainable agriculture can be realized in a way that every farm must be oriented to the process of achieving profitable and efficient production by emphasizing on improving disease management and prevention. Banyuasin Regency is one of the largest regencies that produce corn in the province of South Sumatra. The sub-district that produces the most corn is Tanjung Lago District. Thus, it is necessary to measure social capital in supporting the sustainability of maize farming. This study aims to measure (1) the social capital of corn farmers in Tanjung Lago District; (2) the sustainability of maize farming in Tanjung Lago District. The research location was determined intentionally. Sampling using simple random sampling technique. The data used are primary data and secondary data which were analyzed by tabulation then analyzed mathematically and described descriptively. The results showed that (1) the social capital of farmers in the research location was in the medium category; (2) the opportunity for the sustainability of maize farming in Tanjung Lago District, Banyuasin Regency is worth 54.47%, meaning that it is quite sustainable. Keywords: maize farm, social capital, sustainability